2x-(5-(3x+4))=x-5

Simple and best practice solution for 2x-(5-(3x+4))=x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(5-(3x+4))=x-5 equation:


Simplifying
2x + -1(5 + -1(3x + 4)) = x + -5

Reorder the terms:
2x + -1(5 + -1(4 + 3x)) = x + -5
2x + -1(5 + (4 * -1 + 3x * -1)) = x + -5
2x + -1(5 + (-4 + -3x)) = x + -5

Combine like terms: 5 + -4 = 1
2x + -1(1 + -3x) = x + -5
2x + (1 * -1 + -3x * -1) = x + -5
2x + (-1 + 3x) = x + -5

Reorder the terms:
-1 + 2x + 3x = x + -5

Combine like terms: 2x + 3x = 5x
-1 + 5x = x + -5

Reorder the terms:
-1 + 5x = -5 + x

Solving
-1 + 5x = -5 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-1 + 5x + -1x = -5 + x + -1x

Combine like terms: 5x + -1x = 4x
-1 + 4x = -5 + x + -1x

Combine like terms: x + -1x = 0
-1 + 4x = -5 + 0
-1 + 4x = -5

Add '1' to each side of the equation.
-1 + 1 + 4x = -5 + 1

Combine like terms: -1 + 1 = 0
0 + 4x = -5 + 1
4x = -5 + 1

Combine like terms: -5 + 1 = -4
4x = -4

Divide each side by '4'.
x = -1

Simplifying
x = -1

See similar equations:

| (5c-4c)+(c-3c)= | | 5(12-3x)+x=3(-2x+4) | | x=(x+1)*0.62 | | 0=ln(6x) | | 11=-16+7w | | 79-2x=9-9x | | 4x+9=-54+11x | | b+2=11-b/4 | | 1+8x=-6+x | | 0.4+(0.35e)= | | y=16*6+3 | | -46+8r=8(r-5) | | mn-4m-5n+20= | | y=16*9+9 | | u+9=v | | 4x+22=11x-8 | | 4x+12x=-29+x | | 7d+3d+6d+7=6d | | -8+12=-20 | | 6x-18=3x+11 | | 2x+y=8x+4yforx | | v-3/8=v/3 | | -4x+5=6x | | 36*x^2+4y^2-8y+9z^2-32=0 | | n+9/7=n+3/4 | | 2x+y=8x+4y | | 3(2x-5)+6(3x-1)= | | -10x+5+8x=17 | | 112=2(4+w) | | 9x+8-5x-3=6x+13 | | 5x-4x+3x=32 | | 2x+2=30+6x |

Equations solver categories